The Legal Framework for Technological Protection Measures for Digital Works (A Comparative Analytical Study) - Karim, Abdul Karim Saleh Abdul (Journal of Legal and Political Studies, 2015)
After the technological development and the internet come to existence, the authors and copyright owners try to publish their works on the internet which are protected by copyright laws, But with the many of attack of those rights of works, they feel of need of private protection by another system, so the members of WIPO make a meeting and regulate a system which is called technological measures protection or private protection, this kind of protection is protected by WIPO and also should be by the members of this agreement. Every author can depend on these technological measures with no conflicts between it and the public right of private copy of work according to the fair use system.
Keywords: technological development; copyright; private protection; conflicts